Mission in Latin America: Inculturated Liberation - Irarrázaval, Diego (Missiology, 1992)
Mission in Latin America today-whether inside the continent or abroad— is best conceived as a task of inculturated liberation. It must first of all be about the liberation of all from every form of oppression, whether political, economic, social, cultural, or spiritual; and such liberation must come from the people themselves, in all their cultural diversity and richness. Although this task is one that involves the entire Latin American church, it is best carried out by Latin America's poor, who, in imitation of Jesus, are called to give the gift of their poverty as co-workers with the Spirit in witnessing to God's kingdom.